Development and in vitro evaluations of new decitabine nanocarriers for the treatment of acute myeloid leukemia - Briot T (Dove Medical Press, 2017)
Thomas Briot,1,2 Emilie Roger,1 Nolwenn Lautram,1 Alexis Verger,1 Anne Clavreul,3,4 Frederic Lagarce1,2 1Micro & Nanomédecines Translationelles – MINT, UNIV Angers, INSERM 1066, CNRS 6021, Université Bretagne Loire, MINT IBS-CHU, 2Pharmacy Department, University Hospital of Angers, 3Neurosurgery Department, University Hospital of Angers, 4CRCINA, INSERM, Université de Nantes, Université d’Angers, Angers, France Abstract: Decitabine is a hydrophilic drug that acts by hypomethylating DNA. Decitabine is used in Europe for the treatment of acute myeloid leukemia (AML) in patients aged ≥65 years. However, it can only be administered intravenously due to very low oral bioavailability and a large distribution volume. Oral administration would allow outpatient treatment, improving quality of life and reducing treatment costs. The present study proposes to develop lipid nanocapsules (LNCs), originally designed for lipophilic drugs, to encapsulate decitabine. Two different formulations of LNCs were designed: LNCs based on a high proportion of Transcutol® HP (THP-LNCs) and LNCs associated with a mixture of Transcutol® HP and Tween® 80 (THP-T80-LNCs). The second formulation had a diameter of 26.5±0.5 nm, high encapsulation efficiency (>85%), and a drug payload of 472±64 µg/mL. Decitabine-loaded THP-T80-LNC cytotoxicity was evaluated on two AML cell lines depending on their decitabine resistance: HEL (not resistant) and HL-60 (resistant). The permeability of decitabine-loaded THP-T80-LNCs was also evaluated on Caco-2 cell monolayers. Decitabine cytotoxicity against HEL and HL-60 was higher when decitabine was loaded in THP-T80-LNCs than when free. Apparent permeability on Caco-2 cell monolayers was also increased, suggesting a potentially useful formulation to increase the oral bioavailability of decitabine. Keywords: lipid nanocapsules, acute myeloid leukemia, decitabine, nanomedicine, nanoparticles, oral administration, Caco2 cells